ประสิทธิศักย์และความปลอดภัยของยาบาโคลเฟนในการคงการหยุดดื่มสุราของผู้ป่วยติดสุรา โรงพยาบาลธัญญารักษ์เชียงใหม่ (Efficacy and Safety of Baclofen for Maintenance of Alcohol Abstinence in Alcohol-Dependent Patients, Thanyarak Chiang Mai Hospital) - มิตรมโนชัย, วัลลีย์; วิทยานุกูลลักษณ์, อภิศักดิ์; นิวัฒนนันท์, วิรัตน์ (Academic Psychiatry and Psychology Journal, 2016)
การบริโภคเครื่องดื่มแอลกอฮอล์เป็นปัญหาทางด้านสาธารณสุข เศรษฐกิจและสังคมของประเทศไทย การศึกษานี้มีวัตถุประสงค์เพื่อศึกษาประสิทธิศักย์และความปลอดภัยของยาบาโคลเฟนเปรียบเทียบกับยาหลอกในการคงการหยุดดื่มสุราของผู้ป่วยติดสุราเป็นการศึกษาแบบ randomized, double-blind, placebo-controlled trial ในผู้ป่วยที่มีภาวะติดสุราที่เข้ารับการบำบัดรักษาแบบผู้ป่วยในจนครบระยะเวลารักษา ณ โรงพยาบาลธัญญารักษ์เชียงใหม่ ระหว่างวันที่ 28 พฤศจิกายน 2556 – วันที่ 20 มกราคม 2558 จำนวน 116 คน สุ่มแบ่งผู้ป่วยออกเป็น 2 กลุ่ม กลุ่มละ 58 คน ได้แก่ กลุ่มบาโคลเฟนขนาด 5 มิลลิกรัม หลังอาหาร 3 เวลา เป็นระยะเวลา 3 วัน จากนั้นปรับขนาดเป็น 10 มิลลิกรัม หลังอาหาร 3 เวลา และกลุ่มยาหลอก ให้รับประทานยาเป็นระยะเวลา 12 สัปดาห์ ติดตามผลการศึกษาเป็นระยะเวลา 14 สัปดาห์ โดยเปรียบเทียบการคงการหยุดดื่มสุรา และความปลอดภัยในการใช้ยา วิเคราะห์ข้อมูลแบบ intention-to-treat และแบบ per protocol โดยใช้สถิติ Fisher’s exact test, Mann-Whitney U test, Wilcoxon signed ranks test และ Cox’s proportional hazard regression พบว่าสัปดาห์ที่ 12 กลุ่มบาโคลเฟนมีแนวโน้มคงการหยุดดื่มสุราได้มากกว่ากลุ่มยาหลอก แต่ไม่แตกต่างกันอย่างมีนัยสำคัญทางสถิติ สัปดาห์ที่ 12 กลุ่มบาโคลเฟนจะกลับไปดื่มสุราซ้ำ (relapse) 0.86 เท่าเมื่อเปรียบเทียบกับกลุ่มยาหลอก (HR = 0.86; 95%CI = 0.50-1.48) ซึ่งไม่มีความแตกต่างอย่างมีนัยสำคัญทางสถิติ (p > 0.05) เมื่อเปรียบเทียบจำนวนวันที่ไม่ดื่มสุรา พบว่า กลุ่มบาโคลเฟนมีจำนวนวันที่ไม่ดื่มสุรามากกว่ากลุ่มยาหลอก ซึ่งกลุ่มยาหลอกจะกลับไปดื่มหนักเกินระดับมากกว่ากลุ่มบาโคลเฟน และสัปดาห์ที่ 14 กลุ่มบาโคลเฟนจะกลับมาดื่มสุราน้อยกว่ากลุ่มยาหลอก อาการไม่พึงประสงค์ส่วนใหญ่ ได้แก่ ง่วงนอน อ่อนเพลีย ปวดศีรษะ ปวดเมื่อยกล้ามเนื้อ และปวดข้อ ซึ่งไม่แตกต่างจากการใช้ยาหลอก แต่กลุ่มบาโคลเฟนตรวจพบการทำงานของไตลดลงอย่างมีระดับนัยสำคัญทางสถิติ ดังนั้นการใช้ยาบาโคลเฟนมีแนวโน้มสามารถช่วยคงการหยุดดื่มสุราของผู้ป่วยที่มีภาวการณ์ติดสุราได้มากกว่ายาหลอก แต่ไม่มีนัยสำคัญทางสถิติ ไม่พบอาการไม่พึงประสงค์หลังหยุดรับประทานยา ควรระวังและติดตามการใช้ยาในผู้ป่วยโรคไตอย่างใกล้ชิด Consumption of alcohol causes health, economic and social problems in Thailand. The purpose of this study was to determine the efficacy and safety of baclofen for maintenance of alcohol abstinence in alcohol-dependent patients. The study design was a randomized, double-blind, placebo-controlled trial, conducted in patients that were admitted to Thanyarak Chiang Mai Hospital, where they received addiction therapy and completed the alcohol-dependent treatment program from November 28th, 2013 to January 20th, 2015. One hundred and sixteen patients were randomly divided into 2 groups of 58 patients. One group received baclofen orally at the dose of 5 milligram 3 times a day for 3 days, then 10 milligram 3 times a day for 12 weeks, while the other group received placebo. The assessments were performed at each follow up and at 14 weeks. This study compared maintenance of alcohol abstinence and safety between these two groups. The result of the study was analyzed by using the intention-to-treat analysis and per protocol analysis. A Fisher's exact test, Mann-Whitney U test, Wilcoxon signed ranks test and Cox's proportional hazard regression were used to evaluate the differences between baclofen and placebo group. The results showed that at 12 weeks baclofen exhibited the trend of greater remission rates than that of placebo group but not statistically significance. Baclofen lowered relapse rates 0.86 times (HR = 0.86; 95% CI = 0.50-1.48) compared to placebo group, with no statistically significant difference. Baclofen group had more abstinence days than placebo group. In addition, the number of heavy drinks in placebo group more than that of baclofen group. At the 14th week, baclofen relapse rate was less than that of placebo group. The common adverse reactions found in baclofen group were drowsiness, fatigue, headache, muscle pain and joint pain which were similar to placebo group. But, kidney function in baclofen group has been declined with statistically significant difference. In conclusion, baclofen may help maintain abstinence in alcoholic patients but no statistically significant difference. No withdrawal symptoms were observed. However, alcoholic patients with impaired renal function should have their renal function monitored closely.